Fingerprint-like Analysis of “Nanoantibody” Selection by Phage Display Using Two Helper Phage Variants - Tillib, S.V. (A.I. Gordeyev, 2010)
This paper discusses the selection of mini-antibody (nanoantibody, nanobody® or single domain antibody) sequences of desired specificity by phage display-based method using a generated library of antigen-binding domains of special heavy-chain only antibodies (single-stranded antibodies) of immunized camel. A comprehensive comparison of the efficiency of parallel selection procedures was performed by using the traditional (M13KO7) and modified (with N-terminal deletion in the surface gIII protein) helper phages. These two methods are partly complementary, and by using them in parallel one can significantly improve the selection efficiency. Parallel restriction analysis (fingerprinting) of PCR-amplified cloned sequences coding for mini-antibodies (HMR-analysis) is proposed for identifying individual clones, as a replacement to sequencing (to a certain extent). Using this method, unique data were collected on the selection of mini-antibody variants with the required specificity at various stages of a multi-stage selection procedure. It has been shown that different sequences coding for mini-antibodies are selected in different ways, and that, if this feature is not taken into account, some mini-antibody variants may be lost.